2012
DOI: 10.1016/j.physd.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Bose–Einstein condensates in optical lattices: Mathematical analysis and analytical approximate formulae

Abstract: We show that the GPE with cubic nonlinearity, as a model to describe the one dimensional Bose-Einstein condensates loaded into a harmonically confined optical lattice, presents a set of ground states which is orbitally stable for any value of the self-interaction (attractive and repulsive) parameter and laser intensity. We also derive a new formalism which gives explicit expressions for the minimum energy E min and the associated chemical potential µ 0 . Based on these formulas, we generalize the variational m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Explicit formulae (10), (11) and the approximate relationships ( 14), (15) are among the main results of our work. Nevertheless, more explicit expressions for the order parameter ϕ λ , the energy and the chemical potential as a function of the atom-atom interaction term would be desirable.…”
Section: Applications and Discussion Of The Resultsmentioning
confidence: 81%
“…Explicit formulae (10), (11) and the approximate relationships ( 14), (15) are among the main results of our work. Nevertheless, more explicit expressions for the order parameter ϕ λ , the energy and the chemical potential as a function of the atom-atom interaction term would be desirable.…”
Section: Applications and Discussion Of The Resultsmentioning
confidence: 81%
“…In Ref. 25 it is shown that the perturbation theory for one component reproduces quite well the chemical potential if |Λ 1 | 2. In the present case, the inter-species interaction plays the role as an effective non linear term given by Λ 1 |ψ 1 | 2 + Λ 12 |ψ 2 | 2 .…”
Section: A Chemical Potentialsmentioning
confidence: 99%
“…Notice that if λ 1 = λ 2 , the respective roots are different even in the case V 0 = 0, N 1 = N 2 = N and m 1 = m 2 . Indeed, by subtracting the first equation from the second one in (25), we obtain:…”
Section: Variational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…are reported in [35,40]. In the absence of an optical lattice, namely, for = V 0 0 , in [34][35][36] it was shown that the range of validity of the GPE perturbation approach, equation (7), is limited by a universal criterion given in terms of the dimensionless self-interaction parameter L < | | 3 g J . In the presence of the optical lattice, ¹ V 0 0 , the range of validity of equation ( 14) depends additionally on two parameters, V 0 and d l 0 , yielding a twodimensional parameter map.…”
Section: Excited Statesmentioning
confidence: 99%